2020
DOI: 10.1101/2020.07.06.189829
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SOX9 promotes stress-responsive transcription of VGF nerve growth factor inducible gene in kidney epithelial cells

Abstract: AbstractAcute kidney injury (AKI) is a common clinical condition associated with diverse etiologies and abrupt loss of renal function. In patients with sepsis, rhabdomyolysis, cancer, as well as cardiovascular disorders, the underlying disease or associated therapeutic interventions can cause hypoxic, cytotoxic, and inflammatory insults to renal tubular epithelial cells (RTECs) resulting in the onset of AKI. To uncover stress-responsive disease-modifying genes, here we have car… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…In the present study, we aimed to identify novel diagnostic FRGs genes for AKI based on bioinformatics and machine learning. We analyzed our previously uploaded dataset GSE192883 (Chen et al, 2022) and another mouse dataset GSE153625 (Kim et al, 2020) from GEO database using limma and WGCNA analysis, and identified 885 coDEGs. Enrichment analysis showed that these genes were mainly enriched in Complement and Coagulation Cascades, Cell Cycle, and Oxidoreductase Activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we aimed to identify novel diagnostic FRGs genes for AKI based on bioinformatics and machine learning. We analyzed our previously uploaded dataset GSE192883 (Chen et al, 2022) and another mouse dataset GSE153625 (Kim et al, 2020) from GEO database using limma and WGCNA analysis, and identified 885 coDEGs. Enrichment analysis showed that these genes were mainly enriched in Complement and Coagulation Cascades, Cell Cycle, and Oxidoreductase Activity.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we aimed to identify novel diagnostic ferroptosis-related genes (FRGs) for AKI based on bioinformatics and machine learning. We analyzed our previously uploaded dataset GSE192883 (Chen et al, 2022) and another mouse dataset GSE153625 (Kim et al, 2020) from Gene Expression Omnibus (GEO) database to determine common differentially expressed genes (DEGs) and hub FRGs between AKI and Control specimens. Then, we analyzed their diagnostic value in AKI using machine learning and receiver operator characteristic (ROC) curve analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, multiple upstream and downstream molecules or mechanisms are involved in the renal repair process via Sox9 in AKI. Sox9 drives the upregulation of VGF nerve growth factor in multiple AKI models and acts as a stress-responsive protective gene in TECs (Kim et al, 2020). In IRI and folic acid (FA)-induced AKI models, early growth response 1 (EGR1) can increase Sox9 expression in kidney TECs by directly binding to the promoter of the Sox9 gene, consequently promoting Sox9 cell proliferation by activating the Wnt/β-catenin pathway (Chen et al, 2022).…”
Section: Sox9mentioning
confidence: 99%